Nutritional status, characteristics of housing and breeding of backyard animals as factors associated with enteric parasites in children - Serrano Ramos, David Henry (2020)
The aim of this study was to determine the association of enteroparasitosis in school-age children in the Santa María de Chicmo district (Apurímac, Peru) with the nutritional status, characteristics of the house, and raising of backyard animals. Stool samples were taken from 493 children aged 6-16 years, of both sexes, and their homes were visited to determine their characteristics. The prevalence of enteroparasites was 82.4%, where the highest prevalence corresponded to Entamoeba coli (59.6%), followed by Ascaris lumbricoides (51.1%) and Taenia sp with 33.3%. Other parasites presented prevalence less than 12%. The raising of pigs and chickens was associated with Taenia sp and E. vermicularis, respectively. Defecating in the open field, housing on the edge of crops and on the edge of ditches were associated with E. vermicularis, H. nana and A. lumbricoides. Nutritional status was not associated with parasitosis in schoolchildren. It is concluded that the characteristics of the houses and the raising of backyard animals present characteristics that favour the presentation of intestinal parasitism in children in the Santa María de Chicmo district.